Ta̤zmīn bar salām-i Aḥmad Ra̤zā Ḵẖāṉ : al-maʻrūf, Bahār-i ʻaqīdat - Aḵẖtar al-Ḥāmidī, Sayyid Muḥammad Margẖūb Aḥmad (Maktabah-yi Ra̤zā-yi Muṣ̤tafá, 1979)
Laudatory poem on Prophet Muhammad, in a rare literary form known as 'tazmin' in which the poet inserts his lines into another poet's verse.